Air Asia: Air Asia Berhad / Nurul Atisyah Amran, Nur Fatini Nadziri @ Ismail and Mohammad Amir Suhairi Zuhairy - Amran, Nurul Atisyah; Nadziri @ Ismail, Nur Fatini; Zuhairy, Mohammad Amir Suhairi (2019)
This case study report was done to examine the business of Air Asia in term of work forces, marketing, financials, operations and technology. This report was also done to analysis the problem confronted by Air Asia in maintaining their service as low cost airline in this past years. From the findings, Air Asia is in fact receiving many complaints from customers that are not satisfies with their service. This problem can be divided into two problems, major problem and minor problem. Firstly, the customers are not allowed to change their flight schedule unless they pay for the extra charges. Besides, the seating space inside the cabin is small leading to uncomfortable feeling when the customer want to rest for a long flight duration. In further observation, lack of choices of entertainment on board is also a concern as the customers need to pay for more entertainment program. Therefore, this case study report will evaluating Air Asia in this aspects as well as the problems face to conclude that Air Asia Berhad can be an ideal candidate that can meet the current challenge by the market and satisfy new demands.